PERANAN SALAT DUHA TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI KELAS VIIISMP AN-NADWA ISLAMIC CENTRE BINJAI TAHUN PEMBELAJARAN 2016/2017 - Dedek Nursiti Khodijah (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: The research method used in this thesis uses the approach of explanatory. While the method of datacollection by using observation or observation, in-depth interviews, field notes, and documentation. In addition,the data validity guarantee techniques used in this study include credibility, transferability, dependability, andconfirmability. From the results of this study can be known several things namely as follows: (1) The learningprocess Fiqih the better, along with increasing the intensity of the implementation of Salat Duha conducted santri/ santriah. (2) Students learning outcomes / students after the daily test is seen clearly that students / santriahwho carry out Duha Salat has a value above the KKM that is 75 (3)There is a difference between santri /santriah who diligently performing Salat Duha with the less diligent in performing the Duha Prayer. Santri /santriah who perform Salat Duha have better motivation, diligent memorize Alquran, diligent reading book,and diligent to repeat lesson and have good result of learning result and unidentified violation of school rules.While santriah / santriah who are less diligent in performing Salat Duha tend to be lazy to do the task given, likecheat, lack of attention or less concentrate in learning, less independent, and often sleepy when the learningprocess takes place, and has low value on the learning result and identified Violating school rules such as lateentry into the classroom, skipping class hours, and often not doing homework or teacher-generated duties.